Economic evaluation of cash "plus" interventions for risky sexual behaviour among adolescent girls & young women in low and middle-income countries: a systematic review - Tibini, Vuyolwetu Thembekile (Unknown, 2026)
Background: Adolescent girls and young women (AGYW) are especially susceptible to risky sexual behaviours that increase their risk of HIV infection and other negative consequences related to their reproductive health, especially in low- and middle-income countries (LMICs). Globally, AGYW, who are between the ages of 15-24, are at risk of HIV infection at an average of 4900 every week, while in 2021 AGYW accounted for 63% of all new HIV infections. In response, cash transfer interventions have become a tool to lessen financial vulnerability and provide AGYW with the confidence to make safer decisions regarding their sexual health. However, cash transfer interventions alone might not adequately address the intricate social, biological, and economic issues that AGYW face. As a result, "cash plus" interventions which combine cash with complementary services such as training, health care, and skill development have piqued interest as potentially more effective fixes. The premise of this systematic review is to examine theeconomic evaluations of these "cash plus" programs and their effect on reducing risky sexual behaviours among AGYW in LMICs. Methods: The thesis first implemented a structured literature review. The structured literature delves into the implementation of cash transfers in LMICs and identifies any related shortcomings. Secondly, the structured literature review examines epidemiological evidence of risky sexual behaviours faced by AGYWs in LMICs; these include HIV acquisition, unplanned pregnancy, condomless sex, transactional sex, and multiple sexual partners. Finally, the structured literature review scrutinizes any cash transfer programs that have undergone economic evaluation to address the risky sexual behaviour among AGYWs in LMICs. After the structured literature review was completed, a systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A comprehensive search was performed on several electronic databases, including EbscoHost, PubMed, Cochrane Library, Web of Science, and Scopus, along with relevant grey literature. The review included economic evaluations of cash "plus" interventions aimed at risky sexual behaviour among AGYW in LMICs and studies between 1 January 2000 – 31 December 2023. Studies were screened for eligibility based on pre-defined inclusion criteria, and data were extracted into a synthesis table. Costs were adjusted to 2023 U.S. dollars (USD) to standardize economic evaluations across studies. Full and partial economic evaluations, including cost effectiveness analysis (CEA), cost-utility analysis (CUA), and cost-benefit analysis (CBA), were analysed. The key gaps show how standard cash transfers for AGYW have a limited impact on complex needs, a lack of complementary support, and minimal long-term benefits. Cash Plus addresses these gaps by integrating additional components tailored to AGYW's needs, such as mentorship and skills training, which enhance resilience and support sustainable behavioural changes. However, the economic evaluation of Cash Plus interventions targeting AGYW's risky sexual behaviours in LMICs requires further work. The importance of this work is that it provides evidence of cost- effectiveness, scalability, and long-term economic impact, allowing for informed, resource- efficient decisions on implementing Cash Plus programs in LMICs. Results: This thesis' systematic review retrieved a total of 40 articles, six of which met the inclusion criteria. All these studies, conducted between 2018 and 2022, were based in Sub-Saharan Africa, specifically in Kenya, Uganda, and Liberia. The population covered in the six studies totalled 15,517 AGYW, with interventions targeting a wide age range of 12 to 24 years. The interventions included programs like DREAMS, Empowerment and Livelihood for Adolescents (ELA), Girl Empower Plus (GE+), and Bridge PLUS, among others. Economic evaluations revealed mixed results regarding the cost- effectiveness of the interventions. Five studies performed full economic evaluations using CEA and CBA. One study conducted a partial economic evaluation (cost analysis). The total unit cost for the six units was $2 446,90, but after adjusting for the 2023 value, the amount rose to $2 881,60. Conclusion: The thesis suggests that cash "plus" interventions aimed at reducing risky sexual behaviours among AGYW in Sub-Saharan Africa are cost-effective, particularly over longer time frames. The review highlights the need for further research into the long-term, non-monetary benefits of these interventions, such as improvements in health, education, and social well-being, to fully assess their value. The mixed economic evaluations and inflation-adjusted unit costs highlight the importance of ongoing research and careful resource allocation. The results underscore the importance of targeted, comprehensive strategies in addressing the complex needs of AGYW, while also pointing to the challenges of scaling such interventions in resource constrained environments.